The Effect of Transactional Leadership and Transformational Leadership on Employee Affective Commitment with an Organizational Culture as Moderating Variable: The Case of Religious Court Lahat - Yudha, Ary Puspita; Basyith, Abdul; Yulanda, Delvina (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study, which aims to analyze the influence of transactional and transformational leadership styles on employees’ affective commitment at the Religious Court of Lahat, with organizational culture as a moderating variable, was conducted with a rigorous and thorough research methodology. The background of this research underscores the importance of effective leadership and a healthy organizational culture in fostering employees’ commitment to the institution. The study employed a quantitative approach with a survey technique. Data were collected using a questionnaire that had been meticulously tested for validity and reliability, and then analyzed using Moderated Regression Analysis (MRA). The results show that neither transactional nor transformational leadership styles have a significant effect on employees’ affective commitment. However, organizational culture was found to have a positive and significant impact on affective commitment in the transactional leadership model. In contrast, its effect in the transformational leadership model was not significant. Furthermore, organizational culture does not moderate the relationship between transactional leadership and affective commitment, but it does moderate the relationship between transformational leadership and employees’ affective commitment.